WHEN GRAMMARLY EVALUATES THE TRANSLATION RESULTS: A CORPUS LINGUISTICS - Zaman, Mochamad Nuruz; Edel, Eky Erlanda; Indrayani, Septina (Pascasarjana UM, 2023)
This study investigates the performance of the translation correction tool, Grammarly, in assessing the accuracy of translations; with a descriptive-based qualitative method. The object of this research is the bilingual annual report of PT. Gudang Garam Tbk, which was officially released from the website. Data is collected by analyzing documents and generating data findings. The data is further analyzed by ethnographic methods using domain, taxonomy, componential, and cultural themes. The findings are patterned manually with the classification of translation techniques, which resulted in accurate, inaccurate, and inaccurate translations. This finding reviews the Grammarly evaluating system to assess accuracy so that there are differences between manual analysis and system assessment (translation correction tool). This research contributes to the dynamics of translation learning technology to prioritize manual editing because the system does not have the accuracy to meet industry needs.